Anti-HDV seroprevalence in patients with decompensated liver cirrhosis due to hepatitis B (Annals of Medical Research, 2021)
Aim: Hepatitis B (HBV) and Hepatitis D (HDV) viruses are among the two important causes of end-stage liver disease today. In this study, we aimed to increase HDV awareness in people infected with HBV by examining the prevalence of HDV in patients with end-stage liver disease due to HBV and who were evaluated for liver transplantation.Materials and Methods: The study was designed as a retrospective single-center and cross-sectional. Patients with HBV decompensated liver cirrhosis were divided into two groups as anti-HDV positive and negative. Child-turcott pugh (CTP), Model for End-Stage Liver Disease (MELD) score, complications of liver cirrhosis, viral hepatitis serology, and platelet count variables were statistically compared between the groups.Results: A total of 147 patients with decompensated liver cirrhosis due to HBV were included in the study. Anti-HDV positivity was detected in 46 (31.3%) patients, and anti-HDV negative in 101 (68.7%) patients. The mean age of HDV positive patients (48.39±9.20) was statistically significantly lower than HDV negative (54.37±7.80) patients (p